Why Has the Euro Been so Weak? - Meredith, Guy (International Monetary Fund, 2001)
The weakness of the euro has been surprising given the widely-held expectation that it would be a strong currency. This paper critically examines explanations for the slide in the euro, finding that many are questionable on conceptual or empirical grounds. Two explanations are instead advanced that appear to be consistent both with theory and data. The first originates in the global surge in equity prices since the mid-1990s, which created a demand shock that disproportionately affected the U.S. economy. Model simulations indicate that this can explain the strength of the dollar against other currencies in recent years, accounting for about half of the decline in the effective value of the euro. The other component of euro weakness can be attributed to a mismatch between the demand and supply of euro-denominated assets that arose with the creation of the single currency in 1999. The effect of both these factors should fade over time, although near-term market volatility could be exacerbated by uncertainties about the fundamentals driving currency values